A quantitative exploration of repeated advice-seeking on Reddit's r/relationships - Kang, Bianca Ni Ying (Nanyang Technological University, 2020)
Online spaces for users seeking advice for personal issues have existed since the introduction of the Internet to the public in the 1990s. Today, online advice-seeking is a commonplace activity. However, understanding of this phenomenon is still limited. Much research on advice has focused on the evaluation and outcomes of advice, and on offline exchanges between non-stranger individuals. The current study was thus an exploratory step focused on identifying the factors related to repeated online advice-seeking behaviour. Specifically, the current study examined how (1) user-level differences and (2) differences in forum community reception may be associated with a user deciding to seek advice again on the same advice forum. One years’ worth of postings from a popular relational advice forum (Reddit’s r/relationships) and the posting activity of its users were analysed with the help of computational methods. Results indicated that certain user-level cues were predictive of repeat advice-seeking behaviour. Further analyses highlighted the importance of accounting for gender even when examining behaviour in a pseudonymous faceless environment. Practical implications and future directions were proposed and discussed.